1986
DOI: 10.1016/0022-3115(86)90058-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and lithium purity on corrosion of ferrous alloys in a flowing lithium environment

Abstract: Corrosion data have been obtained on ferritic HT-9 and Fe-9Cr-lMo steel and austenitic Type 316 stainless steel in a flowing lithium environment at temperatures between 372 and 538°C. The corrosion behavior is evaluated by measurements of weight loss as a function of time and temperature. A metallographic characterization of materials exposed to a flowing lithium environment is presented. INFLUENCE OF TEMPERATURE AND LITHIUM PURITY ON CORROSION OF FERROUS ALLOYS IN A FLOWING LITHIUM ENVIRONMENT K. Chopra and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For example, lithium and sodium have important differences with respect to the effects of impurities such as nitrogen, oxygen, and carbon on corrosion and mass transfer behavior. Such differences between sodium and lithium have become clearer in the years since the DeVan and Bagnall review as work in the 1980s progressively revealed the details of the roles of nitrogen and carbon on controlling corrosion and mass transfer in lithiumsteel systems [47][48][49], whereas oxygen is the most important impurity element in sodium [42,44,46,[50][51][52].…”
Section: Corrosion In Liquid Metal Coolantsmentioning
confidence: 99%
“…For example, lithium and sodium have important differences with respect to the effects of impurities such as nitrogen, oxygen, and carbon on corrosion and mass transfer behavior. Such differences between sodium and lithium have become clearer in the years since the DeVan and Bagnall review as work in the 1980s progressively revealed the details of the roles of nitrogen and carbon on controlling corrosion and mass transfer in lithiumsteel systems [47][48][49], whereas oxygen is the most important impurity element in sodium [42,44,46,[50][51][52].…”
Section: Corrosion In Liquid Metal Coolantsmentioning
confidence: 99%
“…A target has been set to limit the concentration of nitrogen and oxygen (which plays a role in the formation of the ternary compounds) in the lithium to <10 wppm each. This value is perceived as safely conservative since the measured corrosion rates of metals exposed to lithium drop below 723 K [79], and 80 wppm seems to be the threshold for the formation of LiN 3 [80], an indispensable step in its chemistry. In turn, deuteron and neutron interaction with lithium generates radioactive products, essentially tritium and 7 Be impurities and dissolved corrosion products become activated when transported through the beam footprint.…”
Section: The Lithium Target Facilitymentioning
confidence: 99%
“…The vacuum in the system is maintained around 10 -5 -10 -6 mbar using a custom-built arc-pump and an adjoined ion-pump. Most parts of the system were fabricated from stainless steel 316 and vacuum gaskets made of soft iron, both compatible with liquid lithium [ 25]. We describe below the system starting from the lithium reservoir and following the lithium flow (Sec.…”
Section: Lilit: Design and Descriptionmentioning
confidence: 99%